Analisis Etika Lingkungan dalam Konservasi dan Pembangunan Berkelanjutan: Tinjauan Literatur Review - Daud Yusuf; Waode Faridawaty; Marini Susanti Hamidun; Sukirman Rahim; Abdul Haris Panai (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Environmental ethics is becoming increasingly relevant in a global context facing climate change, species extinction, and ecosystem degradation. Ethical approaches in conservation decision-making are essential for achieving sustainable development. The need to integrate moral values into conservation policies is becoming urgent due to the conflict between economic and ecological interests. This raises ethical questions regarding the welfare of individual animals versus the broader ecosystem. Although there are several studies on environmental ethics, there is still a lack of comprehensive understanding of how ethical values can be integrated into conservation policies and sustainable development, especially in local contexts like Indonesia. This study analyzes eight studies that explore various ethical approaches in conservation and sustainable development, including local wisdom, animal welfare, and holistic approaches. The analysis shows that environmental ethical values are not only globally relevant but also crucial in local contexts. Indigenous communities play an important role in promoting sustainable conservation practices by integrating local wisdom. These findings highlight the importance of considering ethics in conservation policies, both globally and locally, to ensure long-term environmental sustainability and the welfare of all living beings